Checking timing constraints in software system using AOP - Do, Tuan Anh (ĐHCN, 2017)
In this thesis we propose an approach to dynamic checking a property of real-time software systems, the timing constraints. Checking timing constraints is difficult for some software systems. We can not hook into the system, especially with large systems. From benefit of AOP, we propose an approach to achieve this goal.